ANALYSIS OF ZAKAT GOVERNANCE FOR ECONOMIC EMPOWERMENT THROUGH BINA MANDIRI WIRAUSAHA PROGRAM (CASE STUDY OF LAZIS MUHAMMADIYAH SURABAYA) - Radatiya Chorul Achiroh; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This research aimed to find out the management and distribution of zakat funds in the economic empowerment of the people. The analysis technique used is descriptive with a case study method where this research uses several data collection techniques, namely observation, interviews, and documentation. Funds used in the program are funds obtained from zakat if zakat funds have not been considered sufficient, then, amil will take the funds available in infaq so that they are adequate to be distributed. Afterward, mustahik will be given ten months to return the business capital assistance that has been provided before. The empowerment program was declared successful in reducing the number of poor and disadvantaged people due to the reduction in the number of members from 120 to 80 people. Success in managing incoming ZIS funds is tantamount to success in utilizing ZIS funds for empowering the poor.Keywords: productive zakat, Bina Mandiri Wirausaha Program, economic empowerment, LAZISMU